Chemistry of Antibiotics and Related Drugs - Bhattacharjee, Mrinal K. (Springer International Publishing : Imprint: Springer, 2016)
This textbook discusses how the various types of antibiotics and related drugs work to cure infections. It also delves into the very serious matter of how bacteria are becoming resistant to antibiotics. Appropriate for a one-semester course at either the graduate or advanced undergraduate level, this textbook contains worked examples of experimental procedures and methods of interpreting data.